Improving grammar skills and more - Robles, Rosemarie D. (Sampaloc, Manila, 2005)
This worktext, Improving Grammar Skills and More, is meant to develop interest in learning English among students in the tertiary level. For this purpose, the book has been given a fresher and lighter approach. Topics which were used as springboard to learning grammar are rich, varied, contemporary and follow CHED content requirement
Keywords: English language- Grammar